From Tiberias, with Love: A Collection of Tiberian Hasidism. Volume 2: R. Abraham ha-Kohen of Kalisk - Glazer, Aubrey L. (Academic Studies Press, 2020)
Frontmatter -- Table of Contents -- Acknowledgements -- A. Introduction -- A Spiritual Portrait of R. Abraham Alexander ha-Kohen of Kalisk -- B. Teaching Stories II -- R. Abraham of Kalisk along the Journey to the Promised Land -- C. Reader’s Guide -- 1. R. Abraham Kalisker’s Concept of Communion with God and Man -- 2. From Mythos to Ethos: Contours of a Portrait of R. Abraham of Kalisk -- 3. Moving Mezrich: The Legacy of the Maggid and the Hasidic Community in the Land of Israel -- 4. Theology, Succession, and Social Structure in the Dispute between R. Abraham Kalisker and R. Shne’ur Zalman -- 5. R. Abraham Kalisker’s Critique of Tanya -- 6. The Doctrine of R. Abraham Kalisker: The Path to Communion as the Legacy of the Bnei ‘Aliyah -- 7. Genotextual Performance between Tzaddiqim in Tiberias: R. Abraham of Kalisk’s Encounter with Reb Nachman of Bratzlav -- D. Chesed le-Abraham (Selected Homilies) -- Translators’ Introduction -- Glossary -- Index of Names -- Index of Sources -- Hebrew Critical Edition